1950
DOI: 10.1029/jz055i004p00473
|View full text |Cite
|
Sign up to set email alerts
|

Thunderstorms and the Earth's general electrification

Abstract: In a joint project of the Department of Terrestrial Magnetism, Carnegie Institution of Washington, and the United States Air Force, acceptable electric surveys were made over the tops of 21 thunderstorms in the central United States during July to October, 1948. The purpose of the project was to ascertain whether thunderstorms supply negative electricity to the earth at the rate required to maintain the general negative electrification (negative surface charge) which is almost invariably observed during fair w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

1953
1953
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 3 publications
4
45
1
Order By: Relevance
“…It is assumed that all the points to give the same current as from the erected point, are spaced in rectangular arrays with a separation d. It is also assumed that current below a thundercloud consists only of point-discharge current and is equal to the total current of -0.5 amp. above the thundercloud as observed by Gish and Wait (1950).…”
Section: Calculationssupporting
confidence: 51%
“…It is assumed that all the points to give the same current as from the erected point, are spaced in rectangular arrays with a separation d. It is also assumed that current below a thundercloud consists only of point-discharge current and is equal to the total current of -0.5 amp. above the thundercloud as observed by Gish and Wait (1950).…”
Section: Calculationssupporting
confidence: 51%
“…It consists of a positive charge, 20 to 40 coulombs in size, centred at a height of about 6 km, and a negative charge of approximately the same magnitude centred at a height of about 3 km, that is, near the freezing level. This distribution was originally indicated by field-change measurements (Wilson 1916(Wilson , 1920, definitely established from the alti-electrograph work at Kew Scrase 1937, Simpson andRobinson 1941), and subsequently confirmed by the aeroplane observations of Gish and Wait (1950). Small regions of positive charge towards the base of a thundercloud have also often been noted, and Schonland and Malan (1951) have suggested that these are due to point discharge from the surface of the earth.…”
Section: The Initiation Of Lightning Dischargesmentioning
confidence: 87%
“…It seems unlikely that slow positive field-changes can be due to upward leaders from the positive charge centre near the summit of the thundercloud. Gish and Wait (1950) consider that the discharge from the top of a thunderstorm is in the nature of a small steady current; this would not be observed as causing a field-change with the recording technique described in I, Furthermore, in view of the general increase of conductivity with height, there appears to be little to prevent the vertical extent of any upwardly directed lightning flashes being considerable, and the resulting field-change will then be complex at most of the observing distances concerned.…”
Section: Discharges Not Reaching the Earthmentioning
confidence: 97%
“…They occur mostly in the tropics in the local afternoon and evening. Aircraft and balloon measurements above thunderstorms show that a total current of 0.1-6 A, with an average of 0.4 A, flows from the top of a thunderstorm cell to the ionosphere (Gish and Wait, 1950;Stergis et al, 1957;Vonnegut et al, 1973;Kasemir, 1979). Below a thunderstorm the transfer of charge by point discharge, lightning, precipitation, convection and displacement currents contributes to the net current flowing between the thunderstorm's base and the ground.…”
Section: Global Electric Circuitmentioning
confidence: 98%
“…Figure 3 shows the electric charges carried into the cloud from below by the updraught, constituting an electric current density J M (Roble, 1991). Current (∼ 0.5 A) flowing upward (Gish and Wait, 1950;Blakeslee et al, 1989) from the top of cloud charges the ionosphere, which is a good conductor, and therefore the ionosphere behaves as an equipotential surface having a potential of ∼ 300 kV with respect to the Earth (Wilson, 1916). This happens over 10% of the Earth's surface for all of the ∼ 200 thunderclouds which are active at any time, and which are mainly concentrated over the tropical land masses during the local afternoons.…”
Section: Sources Of Electric Fields In Different Regions and Their Comentioning
confidence: 99%